Analysis of Groundwater Vulnerability to contamination in Wonosari Basin and Gunungsewu Karst Transition Zone, Yogyakarta, Indonesia - Astabella, Relinda Dewi (EDP Sciences, 2023)
The Wonosari Basin and the Gunungsewu Karst Transition Zone have enormous groundwater resources but are hydrogeologically vulnerable to contamination. To achieve sustainable groundwater protection and management, it is imperative to study groundwater vulnerability. Th e research aimed to determine the spatial distribution of groundwater vulnerability in both areas. The COP method, which integrates the concentration of flow (C-Factor), overlaying layer (O-Factor), and precipitation (P-Factor), was used to assess the groundwater vulnerability. Based on the analysis, the groundwater was lowly to very highly vulnerable to contamination. The moderate vulnerability was dominant in both areas. The v*ery low vulnerability was concentrated in the basin, while the low vulnerability was distributed both in the basin (40.43) and the transition zone (32.79). High (12.53) and very high vulnerabilities (5.48) were found in the Gunungsewu Karst Transition Zone, especially in swallow hole recharge area (< 1 km2). The karst transition zone was more highly vulnerable to contamination than Wonosari Basin, a non -karst area. Various known contaminants are by-products of human activities, including nitrates from chemical fertilizers and domestic wastes. To prevent contamination, local governments should actively address the potential sources of contaminants while considering current groundwater vulnerabilities, particularly in the high and very high vulnerability zones. © 2023 EDP Sciences. All rights reserved.